Promoting Healthy Behaviors through Education and Practical Interventions for Disease Prevention in Sungai Pisang - Randy Novirsa; Frima Elda; Yessy Markolinda; Fadilla Azmi (Warta Pengabdian Andalas, 2025)
Sungai Pisang Village is confronted with several public health issues, particularly a high incidence of diseases attributable to inadequate sanitation facilities and unhealthy lifestyle practices. This community-based intervention aimed to improve clean and healthy living behaviors through a combination of educational strategies and practical disease prevention activities. The intervention consisted of structured health education sessions, hands-on demonstrations of hygiene practices, and subsequent evaluations to measure behavioral outcomes and program effectiveness. Active engagement from community members and institutional support from the local health center facilitated program implementation. Findings revealed a significant increase in public awareness and the adoption of clean and healthy living behaviors practices, especially in terms of environmental hygiene, healthy dietary behavior, and preventive health measures. The results suggest that such integrative health promotion efforts can effectively foster sustainable behavioral changes, provided that continuous support from stakeholders is maintained.